Quantification of microplastics in Coptodon rendalli and surface waters of Dikgatlhong Dam, Botswana the first baseline evidence - Ditlhakanyane, Baatshwana Caroline (Environmental technology, 2025)
This study investigated the presence, distribution, and bioaccumulation of microplastics in surface water and Coptodon rendalli at six sites in Dikgatlhong Dam, Botswana: S1 (Tati River Inflow), S2 (Tati River Midway), S3 (Confluence), S4 (Boundary Wall), S5 (Shashe River Midway), and S6 (Shashe River Inflow). All samples were taken in a single day to ensure consistency. To digest organic materials, water samples were processed with the wet peroxide oxidation method, whereas fish tissues were pre-treated with 10% potassium hydroxide (KOH) before going through the same oxidation procedure to extract microplastics efficiently. Surface water microplastic concentrations ranged from 33.59 ± 5.15 n/L (S5) to 78.32 ± 12.83 n/L (S1), and items per fish ranged from 9.46 ± 2.98 (S4) to 19.33 ± 5.87 (S1). The moderate positive association (r = 0.65) between water and fish microplastic levels suggests that water is the primary exposure channel. However, site-specific variations in microplastic size reveal additional factors such as sediment interactions and feeding behaviours. This study emphasizes the importance of focused mitigation methods for managing microplastic pollution and provides a key baseline for future research on microplastic contamination in Botswana's aquatic systems